2020
DOI: 10.1111/ajt.15766
|View full text |Cite
|
Sign up to set email alerts
|

Reassessment of the clinical impact of preformed donor-specific anti-HLA-Cw antibodies in kidney transplantation

Abstract: Abbreviations: +LR, positive likelihood ratio; AMR, antibody-mediated rejection; anti-dHLA, anti-denatured HLA antibodies; anti-nHLA, anti-native HLA antibodies; AUC, area under curve; B-FCXM, B-lymphocyte flow cytometry crossmatch; DSA, donor-specific antibodies; EDTA, ethylenediaminetetraacetic acid; FCXM, flow cytometry crossmatch; −LR, negative likelihood ratio; MFI, mean fluorescence intensity; NPV, negative predictive value; PPV, positive predictive value; ROC, receiver operating characteristic; SAFB, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 33 publications
1
43
0
Order By: Relevance
“…In solid organ transplantation investigations into the contribution of HLA‐C to the induction of an alloimmune response or graft rejection have conflicting results . Aubert and Tran describe an increased risk of antibody mediated rejection in transplant patients sensitised against HLA‐C antigens despite a negative pre‐transplant crossmatch, and Visentin goes on to describe lower graft survival specifically because of HLA‐C sensitisation . However Ling et al were unable to detect increased risk of rejection because of either HLA‐C or ‐DP, suggesting loci with lower antigen expression have less influence on transplant rejection.…”
Section: Discussionmentioning
confidence: 99%
“…In solid organ transplantation investigations into the contribution of HLA‐C to the induction of an alloimmune response or graft rejection have conflicting results . Aubert and Tran describe an increased risk of antibody mediated rejection in transplant patients sensitised against HLA‐C antigens despite a negative pre‐transplant crossmatch, and Visentin goes on to describe lower graft survival specifically because of HLA‐C sensitisation . However Ling et al were unable to detect increased risk of rejection because of either HLA‐C or ‐DP, suggesting loci with lower antigen expression have less influence on transplant rejection.…”
Section: Discussionmentioning
confidence: 99%
“…51 By performing FCXM with cells targeted by only one DSA, either directed at HLA-A, -B or -C, we observed that FCXM results caused by anti-HLA-A and anti-HLA-B antibodies could be correctly predicted by SAFB MFI. 52 Conversely, anti-HLA-C DSA led to random FCXM results, [53][54][55][56][57][58] yet, they did induce a meaningful number of positive FCXM (Table 1).…”
Section: Pathogenicity Of Dsa Directed At Hla-c In Sotmentioning
confidence: 99%
“…Indeed, majority of mAbs (11 out of 17) that bound multiple HLA Class I alleles did not share an eplet among all their top-10 hits (Supplementary Figure 5D). For the remaining 6 mAbs, the top-10 hits did share an eplet for bound HLA-C antigens (Supplementary Figure 5E and F) (Tumer et al, 2013;Visentin et al, 2019;Xu et al, 2012). Thus, shared eplets could not explain the broad reactivity for the majority of the mAbs.…”
Section: In Situ Immunoglobulin Repertoire In Renal Allograft Rejectionmentioning
confidence: 99%